1965
DOI: 10.1113/jphysiol.1965.sp007780
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pco2 acetazolamide and ouabain on volume and composition of choroid‐plexus fluid.

Abstract: A number of investigators have related CO2 metabolism to cerebrospinal-fluid (CSF) formation, e.g. Tschirgi, Frost & Taylor (1954); Fisher & Copenhaver (1959); Oppelt, Maren, Owens & Rall (1963); Pollay & Davson (1963). The present studies were designed to investigate certain aspects of this relation, not as it applies to CSF as a whole, but with respect specifically to the fluid formed by the choroid plexus of the lateral ventricle. The effect on the volume and composition of newly formed choroid-plexus fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1
1

Year Published

1965
1965
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(44 citation statements)
references
References 20 publications
0
42
1
1
Order By: Relevance
“…The only support for this hypothesis in the choroid plexus is that the sodium concentration of freshly secreted c.s.f. appears to be determined by the osmolarity of plasma (Ames et al 1965a). In all these secreting epithelia the basic problem of how solutes and water interact at the two cell membranes remains unresolved: (1) if standing gradients in the lateral spaces (or basal infoldings) account for water movement from the serosal fluid into the cell, what is the nature of the solute pump which generates the standing gradient?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only support for this hypothesis in the choroid plexus is that the sodium concentration of freshly secreted c.s.f. appears to be determined by the osmolarity of plasma (Ames et al 1965a). In all these secreting epithelia the basic problem of how solutes and water interact at the two cell membranes remains unresolved: (1) if standing gradients in the lateral spaces (or basal infoldings) account for water movement from the serosal fluid into the cell, what is the nature of the solute pump which generates the standing gradient?…”
Section: Discussionmentioning
confidence: 99%
“…secretion and plasma bicarbonate during respiratory acidosis or alkalosis (Ames et al 1965a): it further suggests (1) why the c.s.f. adjacent to the choroid plexuses is alkaline with respect to plasma, and (2) a mechanism to explain the homoeostasis of the c.s.f.…”
Section: Ion Transport Across Choroid Plexusmentioning
confidence: 99%
“…production. In previous studies hypercapnia has been found to increase (Ames, Higashi & Nesbett, 1965), decrease (Evans, Reynolds, Reynolds & Saunders, 1976) or have no effect (Hochwald, Malhan & Brown, 1973) on c.s.f. formation.…”
Section: Discussionmentioning
confidence: 99%
“…88,89 The choroid plexus, a site of high-affinity ALDO receptor binding, is involved in the production of cerebrospinal fluid (CSF) and is a target site for ALDO, spironolactone and ouabain, an endogenous digitalis-like substance released by the adrenals and the hypothalamic-pituitary axis. [90][91][92][93][94][95][96][97][98][99] ALDO exerts its biologic actions on epithelial cells by enhancing the activity and number of Na, K ATPase pumps in their apical membrane. A ouabain-sensitive Na, K ATPase is present in the microvilli of the plexus and is involved in the regulation of CSF formation and electrolyte composition (e.g., ouabain reduces CSF production).…”
Section: Central Actions Of Aldosteronementioning
confidence: 99%